ASRO 2021
DOI: 10.36295/asro.2021.24530
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy for uncomplicated simple appendicitis, is it always required?

Abstract: Background: Although Appendectomy is still the classical and standard treatment for acute appendicitis, initial conservative antibiotic only treatmentfor simple un complicated cases have been proposed and tried as a feasible and effective approach.Objecti veof this study was to evaluate the efficacy and outcomes of antibiotics treatment for acute simple uncomplicated appendicitis.Methods: This is a prospective controlled non-randomized study in wh ich a total of 156 patientswhose ages range fro m 16 to 54 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is divisible into three isomers depending on where the nitrogen atom is located inside the ring: 1,2,3-triazole "vicinal triazole"; 1,2,4-triazole "asymmetrical-triazole"; 1,3,4-triazole "symmetrical-triazole n n" [2] . Antioxidant [3,4] , anti-inflammatory [5,6] , anticancer [6,7] , antiviral [8,9] , antifungal [10,11] , antihypertensive, and antibacterial activities [3,4] are only a few of the pharmacologically significant traits displayed by 2,4-triazole. This is important, but it is not all: it has been shown that Schiff bases derived from triazole molecules also exhibit certain biological functions [11] .…”
Section: Introductionmentioning
confidence: 99%
“…It is divisible into three isomers depending on where the nitrogen atom is located inside the ring: 1,2,3-triazole "vicinal triazole"; 1,2,4-triazole "asymmetrical-triazole"; 1,3,4-triazole "symmetrical-triazole n n" [2] . Antioxidant [3,4] , anti-inflammatory [5,6] , anticancer [6,7] , antiviral [8,9] , antifungal [10,11] , antihypertensive, and antibacterial activities [3,4] are only a few of the pharmacologically significant traits displayed by 2,4-triazole. This is important, but it is not all: it has been shown that Schiff bases derived from triazole molecules also exhibit certain biological functions [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Acute appendicitis is the most common abdominal surgical emergency in the world, with a lifetime risk of 8.6% in men and 6.9% in women 3 . There have been many randomized control trials and meta‐analyses examining the advantages and disadvantages of management with antibiotics versus appendicectomy in acute appendicitis 4–13 . The gold standard treatment for the majority of patients with uncomplicated appendicitis is appendicectomy 14 .…”
Section: Introductionmentioning
confidence: 99%
“…3 There have been many randomized control trials and metaanalyses examining the advantages and disadvantages of management with antibiotics versus appendicectomy in acute appendicitis. [4][5][6][7][8][9][10][11][12][13] The gold standard treatment for the majority of patients with uncomplicated appendicitis is appendicectomy. 14 However, there is no consensus on whether transplant surgeons should routinely undertake an incidental appendicectomy (IA) at the time of pancreas transplantation if it has not previously been removed.…”
mentioning
confidence: 99%